Rhamphidoceras saxatilis n. gen. and sp., a micromorph ammonite from the Lower Turonian of Trans-Pecos Texas - Kennedy, W; Cobban, W (1990)
The authors herein describe a previously unrecognized progenic dwarf from the lower Turonian Pseudaspidoceras flexuosum zone fauna of the Chispa Summit Formation in Trans-Pecos Texas. Associated fauna includes: Quitmaniceras reaseri Powell, 1963; Kamerunoceras calvertense Powell, 1963; Mammites powelli Kennedy, Wright, and Hancock, 1987; Vascoceras proprium Reyment, 1954; Fagesia catinus (Mantell, 1822); Wrightoceras munieri (Pervinquiere, 1907); Thomasites adkinsi (Kummel and Decker, 1954); Allocrioceras larvatum (Conrad, 1855); and Mytiloides columbianus (Heinz, 1935). The type species is Rhamphidoceras saxatilis n. gen. and sp. from the lower Turonian Pseudaspidoceras flexuosum zone of Trans-Pecos Texas. -from Authors